Aplikasi Sistem Informasi Penjualan Berbasis Web pada Toko Velg YQ - Josef Bernadi (ComTech: Computer, Mathematics and Engineering Applications, 2013)
The rapid development of information technology gets along with an advance in data processing. Data recording process of sales for company is one of the numerous examples. A system that is able to keep records inventory and profit-loss company is needed to support purchase and sales process. The faster the recording and order process, the more rapid information delivery will be. This research describes factors in making sales information system, payment and reports of YQ wheel store. This research results in a sales information system that facilitates the sales process as well as provides product information of YQ wheel store.